Identification of Material Misstatement and Specific Risk Factors in an Audit of Financial Statements - Žukauskaitė, Deimantė; Daujotaitė, Dalia (Buhalterinės apskaitos teorija ir praktika, 2022)
Recently, due to the changing geopolitical situation, economic instability and vulnerability, practicing auditors are facing new challenges that affect the identification and assessment of risks of material misstatement of financial statements. The purpose of the research is to identify the main factors affecting the risk of material misstatement and specific risks (fraud, accounting estimates, and going concern) that auditors should consider when deciding on the level of the risk of material misstatement of financial statements. To achieve the goal, two tasks were set: to compile lists of factors affecting the risk of material misstatement and specific risks; conduct a questionnaire survey to confirm the compiled lists. The following research methods were used during the research: content analysis and systematization of scientific and normative literature, comparison, logical analysis, questionnaire survey and summarization. As a result of the research, lists of the main factors determining the risk of material misstatement and specific risks were compiled, the completeness of which was confirmed during a questionnaire survey of auditors and auditor assistants working in Lithuanian audit companies. The results of the research show the necessary need for a more thorough assessment of specific risks. Compiled lists of factors determining the risk of material misstatement and specific risks can be useful for auditors of audit companies to assess the risk of material misstatement of financial statements.
Keywords: risk of material misstatement; specific risks; risk factors; audit